Ferrocene‐Based Polymeric Nanoparticles Carrying Doxorubicin for Oncotherapeutic Combination of Chemotherapy and Ferroptosis. Issue 2 (18th November 2022) - Lin, Jundong; Yang, Huikang; Zhang, Yixun; Zou, Fen; He, Huichan; Xie, Wenjie; Zou, Zhihao; Liu, Ren; Xu, Qianfeng; Zhang, Jie; Zhong, Guowei; Li, Yuejiao; et al.
Abstract: Mono‐chemotherapy has significant side effects and unsatisfactory efficacy, limiting its clinical application. Therefore, a combination of multiple treatments is becoming more common in oncotherapy. Chemotherapy combined with the induction of ferroptosis is a potential new oncotherapy. Furthermore, polymeric nanoparticles (NPs) can improve the antitumor efficacy and decrease the toxicity of drugs. Herein, a polymeric NP, mPEG ‐b‐ PPLGFc@Dox, is synthesized to decrease the toxicity of doxorubicin (Dox) and enhance the efficacy of chemotherapy by combining it with the induction of ferroptosis. First, mPEG ‐b‐ PPLGFc@Dox is oxidized by endogenous H2 O2 and releases Dox, which leads to an increase of H2 O2 by breaking the redox balance. The Fe(II) group of ferrocene converts H2 O2 into ·OH, inducing subsequent ferroptosis. Furthermore, glutathione peroxidase 4, a biomarker of ferroptosis, is suppressed and the lipid peroxidation level is elevated in cells incubated with mPEG ‐b‐ PPLGFc@Dox compared to those treated with Dox alone, indicating ferroptosis induction by mPEG ‐b‐ PPLGFc@Dox. In vivo, the antitumor efficacy of mPEG ‐b‐ PPLGFc@Dox is higher than that of free Dox. Moreover, the loss of body weight in mice treated mPEG ‐b‐ PPLGFc@Dox is lower than in those treated with free Dox, indicating that mPEG ‐b‐ PPLGFc@Dox is less toxic than free Dox. In conclusion, mPEG ‐b‐ PPLGFc@Dox not only has higher antitumor efficacy but it reduces the damage to normal tissue. Abstract : A polymeric nanoparticles (NPs), mPEG ‐b‐ PPLGFc@Dox, are performed. First, it can enhance the antitumor efficacy of chemotherapy by combining it with the induction of ferroptosis. Moreover, it can decrease the toxicity of doxorubicin because of the redox‐responsive property of ferrocene in tumor tissue.